Synthesis of As-sintered 60NiTi Parts with a High Open Porosity Level - Khanlaria, K; Ramezani, M; Kelly, P; Cao, P; Neitzert, T (Scielo, 2018)
60NiTi, despite exhibiting attractive chemical and mechanical properties desirable for biomedical applications, has not yet been processed to a porous structure suitable for general bone replacement applications. In this research, elemental Ni and Ti powders were used to process and manufacture 60NiTi parts by employing conventional press-and-sinter method. Blended Ni and Ti powders provided the possibility of liquid formation in the samples during sintering which leaded to an increase in porosity. Different processing parameters such as pressing pressure, sintering temperature, heating rate and sintering holding time were investigated in a systematic way to obtain 60NiTi parts with approximately 30 Vol.% open porosity. Further, the effects of these processing parameters on the microstructure, phase structure and dimensional stability of the as-sintered parts were investigated. Porous parts with satisfactory dimensional stability were obtained in all cases. It was found that applying lower compaction pressure, final sintering temperatures of above 942°C, faster heating rates and shorter sintering time were beneficial in terms of obtaining parts with more open porosities. Samples sintered at a final temperature of 1050°C did not contain any elemental Ni or Ti material and were ready to be solutionized to obtain hard biocompatible 60NiTi parts.
Keywords: 60NiTi; Open porosity; Conventional press-and-sinter; Biomedical